Factors Influencing the Decision to Purchase Subsidized Housing during the COVID-19 Pandemic in South Sulawesi: Sequential Exploratory Design - Sri Rahmi; Heriyanti Mustafa; Gunawan Bata Ilyas; Hasmin Tamsah; Abdul Razak Munir (International Journal of Social Science and Business, 2023)
The decision to buy subsidized houses by low-income people during the COVID-19 pandemic in South Sulawesi Province, Indonesia. This study aims to analyze the factors influencing subsidized housing purchase decisions by low-income people during the COVID-19 pandemic in South Sulawesi Province, Indonesia. The population in this study is subsidized home buyers in Maros Regency, South Sulawesi, who made purchases during the COVID-19 pandemic. The study sample was selected using purposive sampling techniques, where the respondents taken were subsidized home buyers in Maros Regency who made purchases during the COVID-19 pandemic (2019-2021). Data collection was conducted through interviews with subsidized housing developers in Maros District. Interviews were conducted with operations managers, leaders of marketing teams, and marketing administrative staff at subsidized housing developers. Data collected through interviews were processed using confirmatory factor analysis (CFA) and conformity testing models. The main results of this study show that location and quality of service have a significant influence on subsidized home purchase decisions. This shows that location and quality of service are important factors that developers must pay attention to in marketing subsidized houses to low-income people. The results of this study recommend that subsidized housing developers maximize location selection and service quality in marketing subsidized houses.